Hypoxia-Selective Targeting by the Bioreductive Prodrug AQ4N in Patients with Solid Tumors: Results of a Phase I Study - Albertella, Mark R.; Loadman, Paul M.; Jones, Philip H.; Phillips, Roger M.; Rampling, Roy; Burnet, Neil; Alcock, Chris; Anthoney, Alan; Vjaters, Egils; Dunk, Chris R.; Harris, Peter A.; Wong, Alvin; et al. (Clinical cancer research, 2008)
Purpose: AQ4N is a novel bioreductive prodrug under clinical investigation. Preclinical evidence shows that AQ4N penetrates deeply within tumors and undergoes selective activation to form AQ4, a potent topoisomerase II inhibitor, in hypoxic regions of solid tumors. This proof-of-principle, phase I study evaluated the activation, hypoxic selectivity, and safety of AQ4N in patients with advanced solid tumors. Experimental Design: Thirty-two patients with cancer (8 glioblastoma, 9 bladder, 8 head and neck, 6 breast, and 1 cervix) received a single 200 mg/m 2 dose of AQ4N before elective surgery. AQ4 and AQ4N levels in 95 tissues (tumor, healthy tissue) were assessed by liquid chromatography-tandem mass spectrometry. Tissue sections were also analyzed for AQ4 fluorescence using confocal microscopy, and for expression of the hypoxia-regulated glucose transporter, Glut-1. Results: Activated AQ4 was detected in all tumor samples with highest levels present in glioblastoma (mean 1.2 μg/g) and head and neck (mean 0.65 μg/g) tumors; 22 of 32 patients had tumor AQ4 concentrations ≥0.2 μg/g, levels previously shown to be active in preclinical studies. In 24 of 30 tumor samples, AQ4 was detected at higher concentrations than in adjacent normal tissue (tumor to normal ratio range 1.1-63.6); distant skin samples contained very low concentrations of AQ4 (mean 0.037 μg/g). Microscopic evaluation of tumor sections revealed that AQ4 colocalized within regions of Glut-1+ hypoxic cells. Conclusions: AQ4N was activated selectively in hypoxic regions in human solid tumors. Intratumoral concentrations of AQ4 exceeded those required for activity in animal models and support the evaluation of AQ4N as a novel tumor-targeting agent in future clinical studies.